Deliberative Democracy in the Age of Social Media | Democracia deliberativa na Era das Redes Sociais - Völker, Teresa (Revista Publicum, 2019)
Abstract: The potential of the Internet to foster democracy and to strengthen grassroots participation has been widely and controversially discussed. This paper contributes to empirical as well as theoretical research by providing an in-depth analysis of political deliberation in the online sphere. I will explore new paths to improve the quality of political deliberation and to apply and further develop deliberative democratic theory in the age of social media. My vision for a democratic internet is inspired by Fishkin’s (2011; 2018) proposal that large-scale deliberative democracy could solve the democratic trilemma which is the pattern of conflict to realise all three key premises of democracy – political equality, deliberation and mass participation. My research goal is to explore (1) whether the digital transformation provides suitable conditions for the realisation of deliberative democracy on a larger scale and (2) what determines the quality of online deliberation. Based on Habermas and other deliberative democratic scholars, I adapt deliberative democratic theory to the digital context and propose a set of normative standards: rationality, reciprocity, diversity, respect and inclusion. These deliberation criteria function as quality principals to evaluate the current quality and shape of online discussions. The findings highlight that online deliberation is embedded in a multi-layered context and the quality of deliberation is determined by the interplay of the socio-technical infrastructure, the political context, the legal framework and the participants of discourses. The analysis of social media platforms, such as Facebook, indicates that deliberation could be better implemented on publicly administered (new) platforms. Resumo: O potencial das redes sociais para promover a democracia e fortalecer a participação popular tem sido ampla e controversa. Este artigo contribui para pesquisas empíricas e teóricas, fornecendo uma análise aprofundada da deliberação política nas redes sociais. Explorarei novos caminhos para melhorar a qualidade da deliberação política e aplicar e desenvolver a teoria democrática deliberativa na era das redes sociais. Minha visão para uma Internet democrática é inspirada na proposta de Fishkin (2011; 2018) de que a democracia deliberativa em larga escala poderia resolver o trilema democrático que é o padrão de conflito para realizar todas as três premissas principais da democracia - igualdade política, deliberação e participação em massa. Meu objetivo de pesquisa é explorar quais fatores influenciam a qualidade dos discursos políticos e as deliberações em larga escala nas plataformas de rede social. Com base em Habermas e outros estudiosos democráticos deliberativos, adapto a teoria democrática deliberativa ao contexto digital e proponho um conjunto de padrões normativos (racionalidade, reciprocidade, diversidade, respeito e inclusão) para avaliar a qualidade e a forma atuais das discussões online. As conclusões destacam que a deliberação online está inserida em um contexto de várias camadas e a qualidade da deliberação é determinada pela interação da infraestrutura sociotécnica, do contexto político, da estrutura legal e dos participantes dos discursos. A análise de plataformas de rede social, como o Facebook, indica que a deliberação poderia ser melhor implementada em (novas) plataformas administradas publicamente.